2022
DOI: 10.1136/bmjopen-2021-053008
|View full text |Cite
|
Sign up to set email alerts
|

Risk and incidence of cognitive impairment in patients with chronic kidney disease and diabetes: the results from a longitudinal study in a community cohort of patients and an age and gender-matched control cohort in North Wales, UK

Abstract: ObjectivesThe aim of the current investigation is to estimate the incidence and risk for neurocognitive disorders (NCD) in a chronic kidney disease (CKD) cohort with diabetes, compared with an age and sex-matched control cohort.DesignLongitudinal follow-up.SettingDistrict general hospital North Wales, UK.ParticipantsNinety-two patients with CKD and an age and gender-matched sample of 143 controls at baseline and at approximately 36 months.InterventionsCognitive function was assessed in the patients with CKD (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A chronically maintained state of impaired KF may develop into chronic kidney disease (CKD; i.e., eGFR < 60 mL/min/1.73 m 2 for ≥3 months) 6 . Previous studies have related CKD to cognitive decline 14 and a high risk of dementia 15,16 . However, previous studies exploring the association between impaired KF and dementia showed inconsistent results 17–25 .…”
Section: Introductionmentioning
confidence: 99%
“…A chronically maintained state of impaired KF may develop into chronic kidney disease (CKD; i.e., eGFR < 60 mL/min/1.73 m 2 for ≥3 months) 6 . Previous studies have related CKD to cognitive decline 14 and a high risk of dementia 15,16 . However, previous studies exploring the association between impaired KF and dementia showed inconsistent results 17–25 .…”
Section: Introductionmentioning
confidence: 99%
“…Though a tailored self-management approach is supported by meta-analyses, such responses result in lower CSPAM scores [ 54 , 55 ]. It may be particularly challenging for kidney clinicians to support patients on HD to ‘work out new solutions’ or ‘manage the problem on their own,’ because patients on HD are high-risk and dialysis treatment is very complex, with patients being older, frail, multi-morbid and experiencing cognitive impairment and dementia [ 42 , 56 ]. HD patients may prefer to see their specialist team for advice, as general practitioners may not be confident in managing kidney impairment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between renal dysfunction and CI has been repeatedly reported. Clinical studies have suggested that patients with CKD have a higher risk of developing CI in comparison with the normal population [15]. In a longitudinal study, Murray et al found an association between mild albuminuria and worse cognitive function and cognitive decline [16].…”
Section: Discussionmentioning
confidence: 99%